Predicting the level and digital achievement in terms of some body measurements of 2000-meter rowing players in qualifying for the 2023 Asian Cup Championship - Ali, Ayad (Journal of Physical Education, 2024)
The study aimed to identify the relationship of body measurements to the level and digital achievement of 2000-meter rowing players in the 2023 Asian Cup Championship, and to identify the contribution of body measurements to the digital level of 2000-meter rowing players, and to identify the extent of the efficiency of body measurement variables in predicting the level and digital achievement of rowing players, while the research sample was represented by the players of the national rowing team participating in the Asian Cup Championship held in Iran 2023, numbering (15) players who were selected intentionally, as well as the arithmetic mean and deviation Standard, simple correlation coefficient, multiple regression coefficient by regression method, and regression coefficient by stepwise regression method, by using the statistical bag spss to reach the results, and the most important conclusions that appeared were that the body measurements have a high significant correlation with the level and digital achievement of rowers, while it appeared that the body measurements also have high contribution rates to the level and digital achievement of rowers